Bentuk-Bentuk Pemberdayaan Tunanetra Di Panti Sosial Bina Netra “Tuah Sakato” Padang - ALZIKRI ALZIKRI (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2018)
Bina Netra Social House "Tuah Sakato" Padang as a social institution empowerment to change the condition of the blind from helpless to be powerless so as to change the perception of the community that blind people only waiting for a helping hand from others without having to try, to achieve such a thing is not simple, systematic, sustainable and appropriate empowerment with the ability to match the limitations of the visually impaired. the issue is very interesting to be studied in depth with the first aim to reveal the forms of blind spiritual empowerment in the "Tuah Sakato" Panti Social House. Secondly to reveal the forms of blind intellectual empowerment in Bina Netra Social House "Tuah Sakato" Padang. Third to reveal the forms of economic empowerment of the blind at Bina Netra Social House "Tuah Sakato" Padang. fourth to reveal the forms of blind social empowerment in Bina Netra Social House "Tuah Sakato" Padang. by using descriptive qualitative method. The results of this study reveal that; the first spiritual empowerment at Bina Netra Social House "Tuah Sakato" Padang, covers the implementation of worship such as prayers, reading the Qur'an and practice tabligh. both intellectual empowerment at Bina Netra Social Institution "Tuah Sakato" Padang is providing science such as learning braille, KIAB (Braille Arabic Course), typing braille, computer program braille. the third economic empowerment in Panti Sosial Bina Netra "Tuah Sakato" Padang with the awareness, pengkapasitasan, and empowerment through the skills of shiatsu, massage, skill of thunder, craft skills. the fourth social empowerment at Bina Netra Social House "Tuah Sakato" Padang using OM (Mobility Orientation) method recognize environment, move environment, interact with environment, grow mutual help to help.